Managing human side of technology: Skills management - Eng, Poh Hwa; Chew, Boon Cheong; Abdul Hamid, Mohd Syaiful Rizal (Penerbit UTeM Press, 2024)
The book is a new discovery in relevant to the concept of skills management. In general, the field of study focused on the book is about human resource management, specifically in managing the human side of technology (skills management). The authors discuss about the concept of skills management in managing the skilled blue-collar workers when there is a shortage of the skilled blue-collar workers in the automotive industry in Malaysia. In general, the skills management process consists of four stages of activities: skills forecasting and planning, skills development, skills transfer and skills retention. Furthermore, the four stages of activities in the skills management can be conducted from the perspective of an organization and from the perspective of skilled blue-collar workers. The skilled blue-collar workers can increase their skills mastery after going through the four stages of skills management process. The book provides a systematic approach to manage and retain the skilled workers in the automotive industry in Malaysia. The book provides a further insight about the skills management using qualitative approach which is exploratory in nature. Furthermore, the book provides contribution to knowledge to the field of human resource management focusing on the skills management among the skilled blue-collar workers in Malaysia.